Neonicotinoid insecticide seed treatment for the suppression of shoot fly, Atherigona naqvii on spring maize in Punjab - Jindal, Jawala; Kumar, Ravinder (Indian Journal of Plant Protection, 2020)
The neonicotinoid insecticides viz., thiamethoxam 70 WS @ 3, 5, 7 g/kg seed and clothianidin 50 WDG @ 2, 4, 5 g/kg seed along with recommended imidacloprid 600 FS @ 6ml/kg seed were evaluated as seed treatment for the management of shoot fly, Atherigona naqvii in spring sown maize during 2014 and 2015. These seed treatments significantly improved seedling height and promoted root growth. However, did not influence the egg laying by A. naqvii. Significant reduction in shoot fly damage was observed when the seed was treated one day or 21 days before sowing. The mean leaf injury incidence varied from 1.3-7.4 and 4.3-12.9 per cent in one day and 21 days before sowing seed treated plots in comparison to 18.0 and 18.7% in respective untreated control. The mean dead heart incidence in 21 days after germination was significantly lower in all seed treatment combinations (1.3-3.4 and 1.9-3.7%) as compared to untreated control (11.2 and 13.1%) except thiamethoxam 70 WS @ 3 g/kg (5.5 and 5.8%). Similarly, grain yield except thiamethoxam 70 WS @ 3 g/kg seed was also significantly better in both the times of seed treatment than untreated control. So, test insecticides at their respective lower doses as seed treatment i.e. thiamethoxam 70 WS @ 5 g/kg seed and clothianidin 50 WDG @ 2 g/kg seed can be conveniently used in shoot fly management.